Health Adjusted GDP (HAGDP) Measures of the Relationship Between Economic Growth, Health Outcomes and Social Welfare - Matthew Clarke; Sardar M. N. Islam (Center for Economic Studies and ifo Institute (CESifo), 2003)
Welfare economic analysis of health issues and policies can provide well balanced orderings of the state of the economy. This paper provides an innovative framework for welfare economic analysis of the relationships between economic growth, health outcomes and social welfare for both a developing and a developed country. Economic growth can increase health outcomes and social welfare but its influence is limited by biological laws. Further, achieving economic growth may have negative externalities which reduce health outcomes (particularly when biological health limits are reached). A new health adjusted GDP indicator to investigate the relationship between economic growth, health outcomes and social welfare in both a developing and developed country using social choice perspectives is developed in this paper. This new approach to social welfare analysis is also based on cost-benefit analysis and systems analysis and is called the social choice approach. The importance of good health is crucial when determining social welfare. The major limitation of many health-based indicators is that they can fail to adequately consider social welfare issues, such as equity and efficiency. Social choice theory allows optimal health outcomes to be fully considered in terms of equity and efficiency when determining the impact of economic growth on social welfare. Social choice theory incorporates the various social concerns that are not adequately captured using individual preference satisfaction techniques. This paper analyses the health outcomes resulting from economic growth (costs and benefits) using Thailand and Australia as case studies, from 1975 to 1999. Two health adjusted gross domestic product (HAGDP) indices are prepared in this paper by adjusting GDP to reflect the social welfare impacts of achieving economic growth on health outcomes.
Keywords: 330